Un pensiero, una filosofia, un’idea per la città di Yazd |A thinking, a philosophy, an idea for the city of Yazd (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
In 1977, at the end of the elaboration of the Master Plan for the city of Yazd, I asked Ludovico Quaroni to write an introduction to the Plan, to be published in synthesis in a short pamphlet that was meant to present the aims and a selection of the most significant reports [details]. The pamphlet would then be sent to journals and people of culture particularly sensible to the issue of the roots and the identity of the sites in those years of unbridled economic boom of the country. We, those responsible for the Plan, were well aware that its realization was not within the means of the Municipality of Yazd, which possessed neither the financial consistency nor the planning and technical skills to draw up the indispensable Detailed Plans for the realization and supervision. The organized intervention of the State would have been necessary. We presented some concrete proposals in this regard, included in the estimates of the Plan. But we felt the need for the support of a specialized, informed, and qualified opinion; and authoritative. Actually, Farah Pahlavi, Shahbanou of Iran, that is the queen, was our hoped for interlocutor. To her, who had studied architecture in Paris and by vocation and cultural preparation protected the arts, was entrusted also a sort of supervision of the management of Iran’s cities and historical monuments. With Ludovico, therefore, we discussed thoroughly the orientation of the introduction to the Plan and decided on a title; on the base of the Quaroni wrote the essay that I myself translated into Persian. Unfortunately the original text. in Italian, has been lost. But there is still my translation in Farsi. To revive the memory of the thought expressed on that occasion by Ludovico Quaroni on the city, on the oriental city, and on the precious example represented by Yazd, I believed it appropriate then to re-translate from Persian to Italian Quaroni’s text! I hope the reader, despite the ordeals suffered by the original text in its long voyage, will still be able to recognize in it the thought of our maestro. And to enjoy an unexpected return (M. Kowsar).